2017
DOI: 10.1016/j.joca.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E protects rat mesenchymal stem cells against hydrogen peroxide-induced oxidative stress in vitro and improves their therapeutic potential in surgically-induced rat model of osteoarthritis

Abstract: Taken together results of this study demonstrated that Vitamin E pretreated MSCs have an improved ability to impede the progression of OA and thus increased potential to treat OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 49 publications
(49 reference statements)
1
50
0
Order By: Relevance
“…Moreover, a combination of NAC and L‐ascorbic acid 2‐phosphate promoted the growth of MSCs and suppressed oxidative stress‐induced cell death by enhancing mitochondrial integrity and function in vitro under H 2 O 2 ‐induced oxidative stress . Preconditioning with Vitamin E eliminates H 2 O 2 ‐induced injury in MSCs in vitro, and transplantation of these pretreated MSCs increases the proteoglycan content of cartilage matrix for tissue repair of osteoarthritis in vivo . In addition, metformin can be applied to rescue H 2 O 2 ‐induced senescence, long‐term culture‐induced senescence and hypoxia/serum deprivation (Hy/SD)‐induced apoptosis in MSCs …”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a combination of NAC and L‐ascorbic acid 2‐phosphate promoted the growth of MSCs and suppressed oxidative stress‐induced cell death by enhancing mitochondrial integrity and function in vitro under H 2 O 2 ‐induced oxidative stress . Preconditioning with Vitamin E eliminates H 2 O 2 ‐induced injury in MSCs in vitro, and transplantation of these pretreated MSCs increases the proteoglycan content of cartilage matrix for tissue repair of osteoarthritis in vivo . In addition, metformin can be applied to rescue H 2 O 2 ‐induced senescence, long‐term culture‐induced senescence and hypoxia/serum deprivation (Hy/SD)‐induced apoptosis in MSCs …”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…54 induced injury in MSCs in vitro, and transplantation of these pretreated MSCs increases the proteoglycan content of cartilage matrix for tissue repair of osteoarthritis in vivo. 94 In addition, metformin can be applied to rescue H 2 O 2 -induced senescence, longterm culture-induced senescence and hypoxia/serum deprivation (Hy/ SD)-induced apoptosis in MSCs. [95][96][97] Intriguingly, fullerol eliminates cellular ROS, effectively retarding the adipogenic differentiation capacity of MSCs while enhancing their osteogenic differentiation capacity.…”
Section: Pharmaceuticals For Ros Regulation In Mscsmentioning
confidence: 99%
“…11 Hyaline degeneration was reported to be due to cellular apoptosis in rat mesenchymal stem cells. 12 To date, no method to control OIRR has been established. Because lithium inhibits the differentiation of osteoclasts, 2,5,13 lithium may affect OIRR and osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the administration of tocopherol in patients with CKD helped to reduce the risk of cardiovascular complications, increased activity of endogenous antioxidant systems -GPX, catalase [14]. In our previous study [7] we have shown that treatment with an antioxidant lowered the hypoxia-induced cell damage as well as the elevation of HIF-1alpha in vitro [15]. Here we demonstrate that tocopherol administration has a potent effect on hypoxia-induced apoptosis development in children with nephrotic syndrome and subsequent restoration of the proapoptotic factor Bax, BcL-xL and NF-κB activation.…”
Section: Therapeutic Correction Of the Apoptotic Process In Children mentioning
confidence: 78%